Need for uniqueness moderates the effectiveness of different types of scarcity appeals - Wang, Yan; Kong, Shuhong; Li, Meng; Liu, Lin (Frontiers in Psychology, 2022)
Marketers frequently implement scarcity messages in promoting their products. Scarcity due to demand and scarcity due to supply have both been found to influence consumers’ product evaluations positively. However, the differential effects of these two types of scarcity messages have been understudied. Across three studies, we propose and subsequently find that consumers perceive supply-based scarcity products as more unique than demand-based scarcity products. Consequently, in comparison with demand-based scarcity messages, supply-based scarcity messages increase purchase intention for consumers with high need for uniqueness. In contrast, these messages decrease purchase intention for consumers with low need for uniqueness. Our findings contribute to the research on scarcity appeals, uniqueness perception, and need for uniqueness. Our research also suggests that marketers need to implement different types of scarcity appeals to convey uniqueness information and to attract different consumers.